Hispanic and Latino New Orleans : Immigration and Identity since the Eighteenth Century - Sluyter, Andrew, 1958-; Gibson, Annie McNeill; Chaney, James P., 1977-; Watkins, Case, 1976- (Book collections on Project MUSE., 2015)
"Often overlooked in historic studies of New Orleans, the city's Hispanic and Latino populations have contributed significantly to its development. [This book] offers the first scholarly study of these communities in the Crescent City. This ... volume not only explores the evolving role of Hispanics and Latinos in shaping the city's unique cultural identity but also reveals how their history informs the ongoing national debate about immigration"--Page 4 of cover.